The form and content of obasa’s weekly newspaper: the yoruba news (2020)
The Yorùbá News, published d by Oḅ asa,́ co-pioneered journalism, nay publishing, in Yorùbá language in southwestern Nigeria. Based in Ibàdaǹ and published by I ̀lar̀ é ̣ Printers, The Yorùbá News, a bi-lingual serial in English and Yorùbá languages, remarkably had varying contents and wide circulation covering its locale,́ Ibàdaǹ significantly; the southern protectorate, particularly Yorùbá land appreciably; and the entire nation, Nigeria marginally. Published weekly, Oḅasa – the Editor and Proprietor – successfully edited The Yorùbá News for over two decades from 1924 – 1945 when he died. Adopting the Diffusion of Innovations theory, this study examines the form and content of the newspaper. The form examines the structure and layout of the newspaper while the content discusses and evaluates issues covered in the publication. The form of The Yorùbá News is discussed in the context of the print media as a periodical by taking technical cognizance of its physical features: format, design and layout, typography, columns, paper, size and production quality. Content-wise, the paper exhaustively describes the subject matters of The Yorùbá News by dwelling critically on the issues raised, examining in details and critiquing its recurrent subject matters notably: the news stories, editorials, cover, advertorials, news and notes, etc. The inter-dependence of form and content is also examined to bring to the fore the social, cultural, political, and economic values of the maiden Yorùbá Newspaper: The Yorùbá News.